Analisis Putusan Mahkamah Konstitusi Nomor 2/PUU-XX/2022 Tentang Syarat Tidak Pernah Melakukan Perbuatan Tercela Untuk Pencalonan Kepala Daerah Sebagai Putusan Landmark - Ramadhan, Niko Rafael; Amelia, Shelomita Putri; Aliyah, Elirica; Bauw, Irwan; Putri, Khairunnisa Wiladi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Constitutional Court Decision Number 2/PUU-XX/2022 states that the requirement of “never having committed a disgraceful act” for regional head candidacy is contrary to the 1945 Constitution of the Republic of Indonesia (UUD 1945). This research uses a normative juridical method with a statutory approach, and a case approach. The data source in this research is secondary data, including primary legal sources and secondary legal sources. The technique of collecting legal materials is done through literature study. The Constitutional Court's main consideration is that the requirement contradicts the 1945 Constitution, especially the principle of legal equality (Article 27 Paragraph 1), the right to be elected (Articles 28D Paragraph 3 and 28I Paragraph 2), and ignores the rehabilitation mechanism of former prisoners. This multi-interpretive requirement is considered discriminatory because it limits political rights based on the past without considering changes in behavior and the legal process that has been undertaken. As a landmark decision, the Constitutional Court introduced a conditionally unconstitutional approach: ex-convicts are allowed to run for office as long as they have completed their sentence, admit their past honestly to the public, and show remorse. This decision not only invalidates the vague norms in the Pilkada Law, but also forces KPU/Bawaslu to revise administrative practices, guarantees equal political rights without discrimination, and triggers academic discourse on the protection of constitutional rights. Constitutional Court Decision No. 2 / PUU-XX / 2022 confirms that the political rights of ex-convicts are restorative after rehabilitation, restrictions on constitutional rights are only valid through court decisions, without subjective moral discrimination